Political science and the politics of the past: towards an integrated typology of power in pre-and early-modern Southeast Asia - Walker, J. H. (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article explores methodological approaches to the study of pre and early modern state systems in southeast Asia, the study of which has remained, almost exclusively, the preserve of anthropologists, ethnographers, archaeologists and historians. Notwithstanding the regularity with which southeast Asian history and anthropology have been informed by political science methodologies, with a few very notable exceptions, political scientists, themselves, have rarely sought to extend their discipline into the pre- and early-modern eras. Recognising that neither states, power nor politics began in the 1950s, this study aims to redress that situation by seeking, overtly, to integrate a range of political science methodologies into the existing anthropological and historical literature on power and statehood in pre- and early-modern southeast Asia. In doing so it aims also to establish the utility of political science methodologies to the analysis of the remoter past in southeast Asia (and, by implication, to other areas of the world).